Waste less time on Facebook — follow Brilliant.
×

A Stumper

I was trying to solve this problem, but couldn't, even after an hour of toiling! Somebody from Brilliant, please help me!

(√2x-6) + (√x+4)= 5

Note by Jay Steller
3 years ago

No vote yet
1 vote

Comments

Sort by:

Top Newest

(√2x-6) + (√x+4)= 5
condition:x≥3 ==> [(√2x-6) + (√x+4)]²=5² <=> 2x-6 + 2(√2x-6)(√x+4) + x+4 = 25 <=> 3x-2 + 2(√2x²+2x-24) = 25 <=> 2(√2x²+2x-24) =27-3x ==>4(2x²+2x-24) = 27²-162x+9x² <=>x²-170x+825 = 0 <=>(x-5)(x-165) = 0 <=> x=5 or x=165 (satisfies) So, x=5 ; x=165 Jung Hyun Ran · 3 years ago

Log in to reply

What have you tried?

Try squaring the equation, what do you get? Does that get rid of the square roots? Calvin Lin Staff · 3 years ago

Log in to reply

X =5 Manu Attri · 3 years ago

Log in to reply

@Manu Attri How? Can you work it out? Jay Steller · 3 years ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...